Gaps in EU Foreign Policy - Larsen, Henrik. author. aut Link
IX, 98 p. 1 illus.
Keywords: This book argues that theories of European foreign policy are performative: they create the objects they analyse. In this text, Larsen outlines the performativity approach to the role of theories based on the work of Derrida and goes on to examine the performative role of Christopher Hill's concept of Capability-Expectations Gap in the study of European foreign policy. Through examples from relevant literature, Larsen not only demonstrates how this concept sets up standards for the EU as a foreign policy actor (that are not met by most other international actors) but also shows how this curtails analysis of EU foreign policy. The author goes on to discuss how the widespread use of the concept of ‘gap' affects the way in which EU foreign policy has been studied; and that it always produces the same result: the EU is an unfulfilled actor outside the realm of “normal” actors in IR. This volume offers new perspectives on European foreign policy research and advice and serves as an invaluable resource for students of EU foreign policy and, more broadly, European Studies.